Marginal fit comparison of conventional and CAD/CAM techniques of PMMA temporary crown - Achmad Riwandy; Ira Tanti (Indonesian Journal of Prosthodontic, 2023)
Despite the weakness of PMMA as a temporary crown, this material has a high fracture resistance. PMMA can be used for a long time as a temporary and it can replace teeth loss. The marginal fit of the temporary crown must be as precise as that of the definitive crown to prevent irritation of the pulp tissue, inflammation of the periodontal tissues, and also produce an esthetic result. CAD/CAM temporary crown made of PMMA is a new concept in dentistry so it still needs to be investigated regarding the marginal gap in considering the use of conventional PMMA temporary crown. The objective is to review the comparison of the marginal gap of temporary crowns made from PMMA with CAD/CAM technology against conventional method. It is concluded that temporary crowns manufactured by CAD/ CAM method produces a better marginal fit than the conventional method. Polymerization shrinkage is one of the causes of dimensional changes that cause a marginal gap.